TURNING RIVERS INTO LIVING LABORATORIES: ACTION-BASED EDUCATIONAL TOURISM TO ENHANCE YOUTH ECOLOGICAL STEWARDSHIP - Delamontano, Eldo; Endyana, Cipta; Winoto, Yunus; Novianti, Evi (LPPM Universitas Jambi, 2026)
This study examines the influence of action-based educational tourism on bridging the